Preconceptual administration of doxycycline in women with recurrent miscarriage and chronic endometritis: protocol for the Chronic Endometritis and Recurrent Miscarriage (CERM) trial, a multicentre, double-blind, placebo-controlled, adaptive randomised trial with an embedded translational substudy - Martin Underwood; Siobhan Quenby; Joshua Odendaal; Naomi Black; Georgios Bouliotis; Jonathan Guck; Joanne Fisher (BMJ Open)
Introduction Recurrent miscarriage is a common condition with a substantial associated morbidity. A hypothesised cause of recurrent miscarriage is chronic endometritis (CE). The aetiology of CE remains uncertain. An association between CE and recurrent miscarriage has been shown. This study will aim to determine if preconceptual administration of doxycycline, in women with recurrent miscarriages, and CE, reduces first trimester miscarriages, increasing live births.Methods and analysis Chronic Endometritis and Recurrent Miscarriage is a multicentre, double-blind adaptive trial with an embedded translational substudy. Women with a history of two or more consecutive first trimester losses with evidence of CE on endometrial biopsy (defined as ≥5 CD138 positive cells per 10 mm2) will be randomised to oral doxycycline or placebo for 14 days. A subset will be recruited to a mechanistic substudy in which microbial swabs and preintervention/postintervention endometrial samples will be collected. Up to 3062 women recruited from 29 National Health Service (NHS) hospital sites across the UK are expected to be screened with up to 1500 women randomised in a 1:1 ratio. Women with a negative endometrial biopsy (defined as <5 CD138 positive cells per 10 mm2) will also be followed up to test validity of the tool. The primary outcome is live births plus pregnancies ≥24 + 0 weeks gestation at the end of the trial, in the first or subsequent pregnancy. Secondary clinical outcomes will also be assessed. Exploratory outcomes will assess the effect of doxycycline treatment on the endometrial microbiota, the differentiation capacity of the endometrium and the senescent profile of the endometrium with CE.Ethics and dissemination Ethical approval has been obtained from the NHS Research Ethics Committee Northwest-Haydock (19/NW/0462). Written informed consent will be gained from all participants. The results will be published in an open-access peer-reviewed journal and reported in the National Institute for Health and Care Research journals library.Trial registration number ISRCTN23947730.